13y-14⋅(y-1)=3y

Simplify each term.

Combine 13 and y.

y3-14⋅(y-1)=3y

Apply the distributive property.

y3-14y-14⋅-1=3y

Combine y and 14.

y3-y4-14⋅-1=3y

Multiply -14⋅-1.

Multiply -1 by -1.

y3-y4+1(14)=3y

Multiply 14 by 1.

y3-y4+14=3y

y3-y4+14=3y

y3-y4+14=3y

To write y3 as a fraction with a common denominator, multiply by 44.

y3⋅44-y4+14=3y

To write -y4 as a fraction with a common denominator, multiply by 33.

y3⋅44-y4⋅33+14=3y

Write each expression with a common denominator of 12, by multiplying each by an appropriate factor of 1.

Multiply y3 and 44.

y⋅43⋅4-y4⋅33+14=3y

Multiply 3 by 4.

y⋅412-y4⋅33+14=3y

Multiply y4 and 33.

y⋅412-y⋅34⋅3+14=3y

Multiply 4 by 3.

y⋅412-y⋅312+14=3y

y⋅412-y⋅312+14=3y

Combine the numerators over the common denominator.

y⋅4-y⋅312+14=3y

Simplify each term.

Simplify the numerator.

Factor y out of y⋅4-y⋅3.

Factor y out of y⋅4.

y(4)-y⋅312+14=3y

Factor y out of -y⋅3.

y(4)+y(-1⋅3)12+14=3y

Factor y out of y(4)+y(-1⋅3).

y(4-1⋅3)12+14=3y

y(4-1⋅3)12+14=3y

Multiply -1 by 3.

y(4-3)12+14=3y

Subtract 3 from 4.

y⋅112+14=3y

y⋅112+14=3y

Multiply y by 1.

y12+14=3y

y12+14=3y

y12+14=3y

Subtract 3y from both sides of the equation.

y12+14-3y=0

To write -3y as a fraction with a common denominator, multiply by 1212.

y12-3y⋅1212+14=0

Combine -3y and 1212.

y12+-3y⋅1212+14=0

Combine the numerators over the common denominator.

y-3y⋅1212+14=0

Simplify each term.

Simplify the numerator.

Factor y out of y-3y⋅12.

Raise y to the power of 1.

y1-3y⋅1212+14=0

Factor y out of y1.

y⋅1-3y⋅1212+14=0

Factor y out of -3y⋅12.

y⋅1+y(-3⋅12)12+14=0

Factor y out of y⋅1+y(-3⋅12).

y(1-3⋅12)12+14=0

y(1-3⋅12)12+14=0

Multiply -3 by 12.

y(1-36)12+14=0

Subtract 36 from 1.

y⋅-3512+14=0

y⋅-3512+14=0

Move -35 to the left of y.

-35⋅y12+14=0

Move the negative in front of the fraction.

-35y12+14=0

-35y12+14=0

-35y12+14=0

Subtract 14 from both sides of the equation.

-35y12=-14

Multiply both sides of the equation by -1235.

-1235⋅(-35y12)=-1235⋅(-14)

Simplify -1235⋅(-35y12).

Cancel the common factor of 12.

Move the leading negative in -1235 into the numerator.

-1235⋅(-35y12)=-1235⋅(-14)

Move the leading negative in -35y12 into the numerator.

-1235⋅-35y12=-1235⋅(-14)

Factor 12 out of -12.

12(-1)35⋅-35y12=-1235⋅(-14)

Cancel the common factor.

12⋅-135⋅-35y12=-1235⋅(-14)

Rewrite the expression.

-135⋅(-35y)=-1235⋅(-14)

-135⋅(-35y)=-1235⋅(-14)

Cancel the common factor of 35.

Factor 35 out of -35y.

-135⋅(35(-y))=-1235⋅(-14)

Cancel the common factor.

-135⋅(35(-y))=-1235⋅(-14)

Rewrite the expression.

-1⋅(-y)=-1235⋅(-14)

-1⋅(-y)=-1235⋅(-14)

Multiply.

Multiply -1 by -1.

1⋅y=-1235⋅(-14)

Multiply y by 1.

y=-1235⋅(-14)

y=-1235⋅(-14)

y=-1235⋅(-14)

Simplify -1235⋅(-14).

Cancel the common factor of 4.

Move the leading negative in -1235 into the numerator.

y=-1235⋅(-14)

Move the leading negative in -14 into the numerator.

y=-1235⋅-14

Factor 4 out of -12.

y=4(-3)35⋅-14

Cancel the common factor.

y=4⋅-335⋅-14

Rewrite the expression.

y=-335⋅-1

y=-335⋅-1

Combine -335 and -1.

y=-3⋅-135

Multiply -3 by -1.

y=335

y=335

y=335

The result can be shown in multiple forms.

Exact Form:

y=335

Decimal Form:

y=0.0857142‾

Solve for y 1/3y-1/4*(y-1)=3y